Genotoxicity assessment of the flavouring agent, perillaldehyde. (November 2016) - Hobbs, Cheryl A.; Taylor, Sean V.; Beevers, Carol; Lloyd, Melvyn; Bowen, Rachael; Lillford, Lucinda; Maronpot, Robert; Hayashi, Shim-mo
Abstract: Perillaldehyde, a natural monocyclic terpenoid found most abundantly in the herb perilla, has a long history of use as a flavouring ingredient to add spiciness and citrus taste to foods. Previously, it was judged to be safe by several international expert panels. To confirm the safety of flavourings placed on the European Union list of flavourings, perillaldehyde was selected by the European Food Safety Authority as a representative of a subgroup of alicyclic aldehyde flavouring substances to be evaluated for genotoxic potential. Perillaldehyde was tested in a bacterial reverse mutation assay, an in vitro micronucleus assay in human lymphocytes, an HPRT assay in mouse lymphoma cells, and a micronucleus/comet assay in Han Wistar rats. In contrast to previously published results, perillaldehyde induced mutation in Salmonella typhimurium strain TA98 in the absence of metabolic activation. The comet assay was negative for duodenum and weakly positive for liver but only at a hepatotoxic dose of perillaldehyde. All other genotoxicity assays were negative. These data do not provide an indication of any genotoxic potential for perillaldehyde, and they provide the primary basis for recent scientific opinions regarding perillaldehyde genotoxicity announced by several international organizations responsible for safety assessment of food additives and flavourings. Highlights: Perillaldehyde has a long history of use as a flavouring ingredient. EFSA requested testing of perillaldehyde for genotoxic potential. Perillaldehyde was tested in a battery of in vitro and in vivo genotoxicity assays. Results are not indicative of genotoxic potential of perillaldehyde. Results provide a basis for recent international scientific opinion announcements.